Environmental and economic assessment of rainwater harvesting systems under five climatic conditions of Pakistan. (20th June 2020) - Ali, Shahbaz; Zhang, Shouhong; Yue, Tongjia
Abstract: Rainwater harvesting is broadly considered as a promising alternative water resource. In Pakistan, the availability of potable water is a significant issue due to the fast-growing population and urbanization. In this study, a hydro-economic model was developed and applied to investigate water saving and stormwater capture efficiency and financial feasibility of rainwater harvesting systems (RHS) under five climatic regions of Pakistan. Three non-potable water requirements (toilet ﬂushing, garden irrigation, and mixture water requirements) are assessed. According to the results, stormwater capture efficiency is higher for RHS with larger tank size, supplying water for higher water requirement, and located in cities with less rainfall, whereas higher water saving efficiency and reliability are related to larger tank sizes, lower water requirement and situated in humid areas. For example, in Islamabad (humid subtropical climate), a 20 m 3 RHS can capture 33% of the stormwater for garden irrigation and achieve 84% and 88% of water saving efficiency and time reliability, respectively. In Larkana (warm desert climate) a 20 m 3 RHS achieves 33% and 32% of water saving eﬃciency and time reliability for toilet ﬂushing, respectively, but it captures 61% of the stormwater. In humid subtropical, warm semi-arid and Mediterranean continental climate, the economic feasibility of RHS can be attained for appropriately designed RHS; whereas, in cold semi-arid and warm desert areas, the benefit-cost ratio is less than 1.0. Graphical abstract: Image 1 Highlights: A hydro-economic model for rainwater harvesting systems was developed. Environmental and economic performance of RHS was assessed. RHS at eight cities across five climatic regions in Pakistan were investigated. Higher water demand scenarios drive RHS more efficiently. Better performance is expected for RHS with larger tanks and in more humid climate.